2021
DOI: 10.1107/s1600577521003830
|View full text |Cite|
|
Sign up to set email alerts
|

Millisecond timescale reactions observed via X-ray spectroscopy in a 3D microfabricated fused silica mixer

Abstract: Determination of electronic structures during chemical reactions remains challenging in studies which involve reactions in the millisecond timescale, toxic chemicals, and/or anaerobic conditions. In this study, a three-dimensionally (3D) microfabricated microfluidic mixer platform that is compatible with time-resolved X-ray absorption and emission spectroscopy (XAS and XES, respectively) is presented. This platform, to initiate reactions and study their progression, mixes a high flow rate (0.50–1.5 ml min−1) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The lower Q sa condition shows the sample stream fluorescence is nearly completely quenched at x = 0.6 mm. We quantified the degree of quenching by computing the quenched intensity ratio, 𝛽, as a function of spatial location along the jet (Huyke et al, 2021). Briefly, we integrated the quenched and unquenched pixel intensities along the spanwise z-direction, obtained the ratio of these (streamwise) distributions and plotted this ratio as a function of the streamwise coordinate, x.…”
Section: Visualization and Mixing Quantification Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower Q sa condition shows the sample stream fluorescence is nearly completely quenched at x = 0.6 mm. We quantified the degree of quenching by computing the quenched intensity ratio, 𝛽, as a function of spatial location along the jet (Huyke et al, 2021). Briefly, we integrated the quenched and unquenched pixel intensities along the spanwise z-direction, obtained the ratio of these (streamwise) distributions and plotted this ratio as a function of the streamwise coordinate, x.…”
Section: Visualization and Mixing Quantification Experimentsmentioning
confidence: 99%
“…protein folding) (Pollack et al., 1999). In large part because of the line-of-sight integrating nature of X-ray methods, the mixing function of these microfluidic devices has been achieved using three-dimensional (3-D) hydrodynamic focusing (Huyke et al., 2020, 2021; Plumridge et al., 2018). Furthermore, the sample injection task is increasingly achieved using microfluidic devices that produce free jets to accommodate the highly powerful radiation of next-generation X-ray sources (Crissman et al., 2022; Ishigami et al., 2019; Knoška et al., 2020; Wang, Weierstall, Pollack, & Spence, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the Kβ XES spectra to the spin on the metal center , has been widely used to determine spin and oxidation states, e.g., to track excited-state intermediates in time-resolved experiments or reactive intermediates of chemical and biological reactions. Beyond the probe of local spin, some studies indicated that the Kβ XES can also be used to probe the orbital covalency. The energy difference between Kβ 1,3 and Kβ′ was found to be proportional to the nominal spin state that can be further modulated by the orbital covalency, or the effective 3d spin, , as the energy splitting is connected to the effective spin on the metal center and hence the magnitude of exchange interactions. When going to lower-spin states, the Kβ 1,3 –Kβ′ energy splitting becomes more and more challenging to determine due to the reduced intensity of the Kβ′ feature and the strong intensity of the main line.…”
Section: Introductionmentioning
confidence: 99%
“…Huyke et al employ a flow focusing geometry with a polyimide capillary providing X-ray access, however the relatively long path length through the sheath fluid renders this device unsuitable for tender X-ray studies. 50 Chan et al combined etched-silicon flow-focusing channels with SiN x windows to study the kinetics of a nanocrystal cation exchange. 51 The high aspect ratio of the channel employed is not designed for investigating diffusion reactions, and the addition of a SU8 layer in the beam path and deep channel would also lead to high attenuation of tender X-rays.…”
Section: Introductionmentioning
confidence: 99%